Injectable gellan gum-based hydrogels for intervertebral disc regeneration - Silva-Correia, Joana (2011)
Intervertebral disc (IVD) degeneration is a challenging pathology that, due to the inefficiency of the current treatments, urgently demands for the development of new regenerative approaches[1]. The best viable implant material for nucleus pulposus (NP) regeneration has yet to be identified, but it is believed that biodegradable hydrogelbased materials are promising candidates[2]. In this work, we are proposing the use of ionic- and photocrosslinked methacrylated gellan gum (GG-MA) hydrogels as potential acellular and cellular injectable scaffolds for IVD regeneration.